Efficiency of Bacillus pseudomycoides RAY21 and Bacillus subtilis CYA27 Endospore Formulation on Biochar and Oil Spill Dispersant - Rahmatullah, Rifki; Anwar, Saiful; Yani, Mohamad; Firlandiana, Maulidi (HAYATI Journal of Biosciences, 2025)
Bacillus sp. is well known for its functional capabilities such as solubilizing phosphorus (P) and potassium (K), and fixing nitrogen (N2). These bacteria can form endospores under stressed conditions, allowing long-term survival and application in biotechnological fields. This study aims to isolate Bacillus sp. capable of forming endospores and evaluates their viability on different carriers, specifically biochar and oil spill dispersant (OSD), to enhance biodegradation in contaminated environments. Soil samples from the bamboo rhizosphere were heat-shocked to isolate endospore-forming Bacillus strains, with the isolate identified as Bacillus pseudomycoides RAY21 through 16S rRNA sequencing. This strain exhibited Gram-positive characteristics, formed endospores, and demonstrated potential on various media such as Pikovskaya, Alexandrov, and N-Free Mannitol. The physiological characterization indicated optimal growth in a pH range of 6-8, salinity up to 3.5%, and thermophilic properties. Endospores from B. pseudomycoides RAY21 and B. subtilis CYA27 were tested on biochar and OSD as carriers. The results showed that endospores adhered better to biochar, but their viability was more stable in OSD over time. Notably, B. pseudomycoides RAY21 on OSD degraded 23.43% of total petroleum hydrocarbons (TPH), outperforming B. subtilis CYA27 (21.62%). In conclusion, the study demonstrates the potential of using Bacillus endospores on OSD as an effective carrier for bioremediation, particularly in degrading petroleum hydrocarbons. Future research should focus on optimizing carrier materials and exploring field-scale applications for enhanced environmental cleanup.